2003
DOI: 10.1007/s00059-003-2495-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Thermography

Abstract: Arteriosclerosis is an inflammatory disease. Inflammatory processes play a role in the initiation of plaque development and the early stages of the disease as well as in complex plaques and complications such as intraarterial thrombosis. A method to detect inflammation in coronary arteries has the potential to characterize both local and systemic activation of arteriosclerotic plaque disease. It could help to define in more detail what constitutes a vulnerable plaque or vulnerable vessel and thus improve the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
8
1
1
Order By: Relevance
“…More recently, several other groups have reported similar fi ndings, albeit lower degrees of thermal heterogeneity in plaques of CAD patients [18][19][20]. These differences may be attributable to the different types of thermistors used to measure plaque temperature and differences in the patient populations studied, including the use of statin medications, which have been shown to reduce thermal heterogeneity [21][22][23].…”
Section: Clinical Studiesmentioning
confidence: 57%
“…More recently, several other groups have reported similar fi ndings, albeit lower degrees of thermal heterogeneity in plaques of CAD patients [18][19][20]. These differences may be attributable to the different types of thermistors used to measure plaque temperature and differences in the patient populations studied, including the use of statin medications, which have been shown to reduce thermal heterogeneity [21][22][23].…”
Section: Clinical Studiesmentioning
confidence: 57%
“…12,22,24,[27][28][29][30][31][32][33][34] These methods are complementary to techniques that measure biomechanical properties because they provide structural and compositional information that contributes to plaque stability. Intravascular ultrasound elastography facilitates atherosclerotic plaque characterization by computing local strains in the plaque in response to intraluminal pressure differentials exerted on the arterial wall.…”
Section: Other Plaque Characterization Methodsmentioning
confidence: 99%
“…Another study showed increased plaque temperature for an extended period after myocardial infarction, indicating that the inflammatory process is sustained after plaque rupture [22]. To further investigate the role of inflammation in arterial heat production, Schmermund et al [23] used a non-occluding thermography catheter (Volcano Therapeutics, Rancho Cordova, CA). Focal temperature heterogeneity was observed in 50% of patients with acute coronary syndrome (ACS) and 27% of patients with SA [23].…”
Section: Human In Vivo Intracoronary Thermography Studiesmentioning
confidence: 98%
“…To further investigate the role of inflammation in arterial heat production, Schmermund et al [23] used a non-occluding thermography catheter (Volcano Therapeutics, Rancho Cordova, CA). Focal temperature heterogeneity was observed in 50% of patients with acute coronary syndrome (ACS) and 27% of patients with SA [23]. Wainstein et al [24] used a different thermography catheter (ThermoCoil Guidewire), and patients were also evaluated by intravascular ultrasound.…”
Section: Human In Vivo Intracoronary Thermography Studiesmentioning
confidence: 99%